Improving the Assessment of the Tourism Potential of the Russian Arctic - Myakshin, Vladimir N.; Shaparov, Alexander E.; Tikhanova, Daria V. (Economy of Regions, 2021)
The development of the domestic tourism market, including the Arctic zone of the Russian Federation, is important for overcoming the consequences of the economic crisis caused by the COVID-19 pandemic. A comprehensive and reliable methodology for assessing the tourism potential is necessary for effective decision making and attracting tourists. Based on the analysis of international and Russian experience of assessing tourist destinations, we identified the shortcomings of the existing methods and substantiated the necessity of a nuanced approach to assessing the tourism potential of regions using authors’ balanced scorecard. Our methodology relies on the balanced approach, demonstrating the compliance of the assessment results with the interests of tourism stakeholders. The developed method considers information needs and main interests of tourists, business representatives, regional population and authorities. Based on key parameters of the tourism potential of the Arctic zone, we defined the structure of the balanced scorecard (economic, infrastructural and cultural-natural aspects) using systems and structural-functional analysis. Further, using the multivariate mean (with target values of indicators as a standardised coefficient), we calculated integral indicators, eliminating the influence of dynamics of other regions on the assessment results. Structural and comparative analysis of a matrix of integral indicators allowed us to examine the dynamics of the tourism potential of the Russian Arctic and ways to improve it (on the example of Arkhangelsk oblast). Correlation analysis of the relations between the tourism potential and tourist flows within a time lag confirms the reliability of the developed methodology. Research results can be used by authorities managing the Russian Arctic for identifying the ways to increase its tourism potential.